60.6k views
0 votes
⎩ ⎪ ⎪ ⎨ ⎪ ⎪ ⎧ ​ a(1)=−13 a(n)=a(n−1)+4 ​ Find the 2nd2^{\text{nd}} 2 nd 2, start superscript, start text, n, d, end text, end superscript term in the sequence

2 Answers

4 votes

In the sequence a(1) = -13 and a(n) = a(n-1) + 4, the 2nd term is -9. The sequence progresses with a constant increase of 4 between terms: -13, -9, -5, -1, 3, ....

The sequence defined by
\(a(1) = -13\) and
\(a(n) = a(n-1) + 4\) forms an arithmetic progression.

To find the 2nd term a(2), we apply the recurrence relation:
\(a(2) = a(1) + 4 = -13 + 4 = -9\).

This yields the second term in the sequence as -9. Each subsequent term in the sequence can be obtained by adding 4 to the previous term.

The progression unfolds as follows:
-13, -9, -5, -1, 3, \ldots.

The common difference between consecutive terms is 4, indicating a steady arithmetic increase.

Understanding the recurrence relation allows for the determination of specific terms and the overall behavior of the sequence.

Therefore, the 2nd term in the sequence is -9.

User Bedrin
by
4.6k points
4 votes

Answer:

a(2) = -9

Explanation:

It looks like you want the 2nd term in the arithmetic sequence defined by the recursive formula ...

  • a(1) = -13
  • a(n) = a(n -1) +4

Using the formula with n=2, we have ...

a(2) = a(1) +4

a(2) = -13 +4 . . . . substitute the value of a(1)

a(2) = -9

User Opes
by
5.9k points